Step-by-step explanation:
The question involves dividing radicals
To resolve the question, we will follow the steps below
Step 1: Write the expression
![√(50x^3)/√(32x^2)](https://img.qammunity.org/2023/formulas/mathematics/college/qgc3uob4v5xcfzf2kpqygnw0ku4tl4c61w.png)
Step 2: simplify the expression in parts and apply the laws
![\begin{gathered} √(50x^3)=√(25*2* x^2* x) \\ =√(25*2* x^2* x)=√(5^2*2* x^2* x)=√(5^2)*√(x^2)*√(2x) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/nq5n7elzwdbi8tn50wnocdym7av3wwh0qx.png)
Thus
![\begin{gathered} √(50x^3)=√(5^2)*√(x^2)*√(2x)=5* x*√(2x) \\ Therefore \\ √(50x^3)=5x√(2x) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/nhvhspj3etxacyvmlb9xnt7q3t4i1gvm42.png)
For the second part
![√(32x^2)=√(16*2* x^2)](https://img.qammunity.org/2023/formulas/mathematics/college/i7i5hd94a7cp1v3x9h8irmnpy9i50yvnt0.png)
simplifying further
![√(16*2* x^2)=√(16)*√(x^2)*√(2)](https://img.qammunity.org/2023/formulas/mathematics/college/b0twli2m7n2lkbihm6u488hlqov539ya6d.png)
Hence, we have
![√(16)*√(x^2)*√(2)=4* x*√(2)=4x√(2)](https://img.qammunity.org/2023/formulas/mathematics/college/wug017ev3tbyv9efrzjstmgagii6sui3g3.png)
Finally, we will combine the simplified terms, so that we will have
![√(50x^3)/√(32x^2)=5x√(2x)/4x√(2)](https://img.qammunity.org/2023/formulas/mathematics/college/xj6rh62t8ooyf03pou5mfxooobq086g3gk.png)
Hence, we will have
![(5x√(2x))/(4x√(2))=(5)/(4)*(x)/(x)*(√(2))/(√(2))*(√(x))/(1)](https://img.qammunity.org/2023/formulas/mathematics/college/dpv5svuwwp3wrbuxpf0b10r6rwnqazjltn.png)
By canceling out the common parts, we will have the answer to be
![(5)/(4)√(x)](https://img.qammunity.org/2023/formulas/mathematics/college/y3xhkl2j7s3ihhx5mwq5qkfwm6ll1ukr66.png)